ANALISIS KEMAMPUAN DISPOSISI MATEMATIS PADA PEMBELAJARAN MATEMATIKA SISWA SDN 01 KEBONSARI KABUPATEN TEMANGGUNG SEMESTER GENAP TAHUN AJARAN 2019/2020 - Miranda Ramadhani; Sukamto Sukamto; Aries Tika Damayani (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2020)
The aim of the research is analizing the mathematical disposition abilities of students of SDN 01 Kebonsari Temanggung periode 2019/2020. This research uses qualitative methods in descriptions. The study population was 25 high-grade students at SDN 01 Kebonsari Temanggung. Data sourced from the results of observations, interviews and documentation. The results showed that the mathematical disposition ability of high grade students of SDN 01 Kebonsari Temanggung was in the medium category. The average results of the mathematical disposition questionnare on high class students was 37.92%, while the results of student observations when doing take home exercise were 48.89%. The conclusion of this study is that almost half of the students already have mathematical disposition abilities in learning mathematics. However, the students's mathematical disposition skills still need to be improved. The suggestion in this study is that teachers have to pay more attention in the ability of students' dispositions, there must be cooperation between guardians at home and teachers to control students both in class and at home, so that students get more attention in affective, cognitive and psychomotor, especially mathematical disposition.